Electrospinning technology in water treatment applications: Review article - Ahmed H. Oleiwi; Akram R. Jabur; Qusay F. Alsalhy (Desalination and Water Treatment)
Polymeric fibers have emerged as an intriguing medium for constructing structures utilized in several industrial fields specially water treatment fields. Fibrous structures possess particular characteristics due to their extensive surface area, rendering them appealing for numerous applications. Spinning techniques have received significant focus in tissue engineering, resulting in the creation of polymeric fibers. Polymeric nanofibers with nanometer-scale diameters provide much greater surface areas and a high surface area to volume ratio, rendering them highly efficient by promoting improved surface functionalization. Electrospinning is an innovative and effective method for producing nanofibers. The electrospinning technology facilitates a uniform pore size, regarded as a crucial property of membranes. Consequently, water purification applications have employed electrospun nanofibrous membranes. Membrane distillation and nanofiltration procedures extensively employ this approach to produce membranes that eliminate impurities. This review study focuses on finding the best settings for certain factors and creating polymeric solutions for making special, nanofibrous, non-woven membranes and changing the surface of these membranes for use in water treatment technology.